Data from: Undersowing oats with clovers supports pollinators and suppresses arable weeds without reducing yields - Boetzl, Fabian; Lundin, Ola (Swedish University of Agricultural Sciences, 2023)
We studied the effects of undersowing oats with a mixture of three annual clovers species across different aspects of cropping system multi-functionality using 26 observation plots in a paired field design with 13 fields. We investigated 16 below-and above-ground ecosystem service indicators related to soil mineral nitrogen, arable weed control, pollination, disease and pest pressures, natural pest control and crop yield. We measured each of the 16 ecosystem service indicators in an intercropped and in a control treatment with identical management. Some indicators were measured before and after the experiment in both treatments to assess the magnitude of change by the treatment.
For further information, see methods in the publication Boetzl et al. (2023) Undersowing oats with clovers supports pollinators and suppresses arable weeds without reducing yields. Journal of Applied Ecology.

The data in the 'combined_dataset.csv' file have information on different ecosystem service indicators collected in 13 fields ('field_ID') and two treatments per field (intercropped and control). 27 rows.

The 16 ecosystem service indicators contained are: soil mineral nitrogen (before and after the experiment), arable weed cover, arable weed biomass, granivorous carabid beetle density, flower cover, pollinator density, root disease severity (before and after the experiment), root-feeding nematode density (before and after the experiment), cereal leaf beetle damage, predatory nematode density (before and after the experiment), predatory carabid beetle density, staphylinid beetle density, spider density, predation rates on the soil level, oat yield and oat yield nitrogen content. Additionally, the biomass of undersown clovers in the intercropped treatment, the area covered by the intercropped treatment, the field size and the arable land cover in 1 km radius around the oat field are stated.

Data innehåller information om 16 ekosystemtjänst-indikatorer som mättes i 13 fält med insådder av en blandning av klöverarter på en del av fältet. Alla mätningar gjordes i den insådda ytan samt i en närliggande kontroll utan insådd på samma fält. En mer utförlig beskrivning ges på engelska.

Data i filen 'combined_dataset.csv' innehåller information om olika ekosystemtjänst-indikatorer som samlades in från 13 fält ('field_ID') och två olika behandlingar per fält (intercropped and control). 27 rader. En utförligare beskrivning ges på den engelska sidan.
Data från: Klöver som bottengröda i havre stödjer pollinatörer och dämpar ogrästrycket utan att minska skörden
Keywords: ecosystem services; ekosystemtjänster; Habitats and biotopes; Naturtyper och biotoper; cereal crops; sädesslag; bumblebees; humlor; nematodes; rundmaskar; intercropping; samodling; ecological intensification; ekologisk intensifiering; ground dwelling predators; marklevande rovdjur; carabid beetles; jordlöpare; Biological Sciences; Biologi; Ecology; Ekologi; Agricultural and Veterinary sciences; Lantbruksvetenskap och veterinärmedicin; Agricultural Science; Jordbruksvetenskap; Farming; Areella näringar; Environment; Miljö